SAH derived potent and selective EZH2 inhibitors. Issue 7 (1st April 2015) - Kung, Pei-Pei; Huang, Buwen; Zehnder, Luke; Tatlock, John; Bingham, Patrick; Krivacic, Cody; Gajiwala, Ketan; Diehl, Wade; Yu, Xiu; Maegley, Karen A.
Graphical abstract: Abstract: A series of novel enhancer of zeste homolog 2 (EZH2) inhibitors was designed based on the chemical structure of the histone methyltransferase (HMT) inhibitor SAH ( S -adenosyl-l -homocysteine). These nucleoside-based EZH2 inhibitors blocked the methylation of nucleosomes at H3K27 in biochemical assays employing both WT PRC2 complex as well as a Y641N mutant PRC2 complex. The most potent compound, 27, displayed IC50 's against both complexes of 270 nM and 70 nM, respectively. To our knowledge, compound27 is the most potent SAH-derived inhibitor of the EZH2 PRC2 complex yet identified. This compound also displayed improved potency, lipophilic efficiency (LipE), and selectivity profile against other lysine methyltransferases compared with SAH.